ANALISIS SISTEM INFORMASI AKUNTANSI DALAM MENUNJANG EFEKTIVITAS PENGENDALIAN INTERNAL PADA SMKN 1 RENGASDENGKLOK - Titin Suhartini; Ika Sari (Bajang Institute, 2023)
This study aims to determine whether the accounting information system is appropriate in supporting the effectiveness of internal control at SMKN 1 Rengasdengklok. The approach taken in this study is a qualitative approach. The population in this study were employees of SMKN 1 Rengasdengklok with 11 respondents. The data analysis technique used in this research is by comparing the findings of the field with the theory of accounting information systems. The results of this study indicate that the accounting information system does not fully support the effectiveness of internal control, systems that are not yet in accordance with Mulyadi's (2016) theoretical study are segregation of duties, accounting system procedures and accounting records